Density of N\(_2\) Active Species in N\(_2\) Dielectric Barrier Discharge Afterglows by Optical Spectroscopy at Atmospheric Gas Pressure - Clément, Frank; Held, Bernard; Ricard, André (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Dielectric Barrier Discharges (DBD) have been used to develop Cold Atmospheric Plasmas and more specifically nitrogen afterglows. The DBD afterglow has been investigated by emission spectroscopy from the VUV (200-300 nm) up to the near IR (1 \(μ\)m) ranges. A kinetics scheme allowed to determine numerous N2 active species densities. The obtained densities decreased slowly in the afterglow time of (1- 10)10-3s with mean values of 1015 cm-3 for N- atoms, 1012 cm-3 for N2(A) molecules, 1011 cm-3 for O- atoms (coming from air in impurity) and 1010 cm-3 for N2(B,0) radiative molecules. The other excited species (N2(B,11), N2 (X,v>4), NO(X, A, B) and O1S.N2 were found at a lower density between 106 and 108 cm-3.